The Role of the Factor V Leiden Mutation in Osteonecrosis of the Hip. (September 2013) - Glueck, Charles J.; Freiberg, Richard A.; Boriel, Gail; Khan, Zia; Brar, Amanpreet; Padda, Jagjit; Wang, Ping
We examined the hypothesis that the factor V Leiden (FVL) and G20101A prothrombin gene mutations are commonly associated with hip osteonecrosis. We prospectively evaluated 244 consecutively referred adults with osteonecrosis (ON), 161 idiopathic and 83 secondary. Cases (n = 244) did not differ from 104 normal controls by race. Of the 244 patients, 23 (9.4%) were FVL heterozygotes versus 2 of 104 controls (1.9%), P = .013, risk ratio (RR) = 4.90, 95% confidence interval (CI) 1.18 to 20.4. Of the 161 patients with idiopathic ON, 15 (9.3%) were FVL heterozygotes versus 2 of 104 normal controls (1.9%), P = .017, RR = 4.84, 95% CI 1.13 to 20.8. Of the 83 patients with secondary ON, 8 (9.6%) FVL heterozygotes versus 2 of 104 normal controls (1.9%), P = .024, RR = 5.01, 95% CI 1.09 to 23.0. Prothrombin gene heterozygosity in normal controls (2.9%) did not differ from ON cases (3.4%), P = 1.0. The thrombophilic FVL mutation is commonly associated with and may be pathoetiologic for hip osteonecrosis.